1992
DOI: 10.1093/oxfordjournals.eurheartj.a060285
|View full text |Cite
|
Sign up to set email alerts
|

Native valve infective endocarditis in the general population: a 10-year survey of the clinical picture during the 1980s

Abstract: In a population of 930,000 inhabitants all records of native valve infective endocarditis diagnosed in the decade 1980-89 were reviewed. Using strict case definitions 132 clinically well-defined or post-mortem diagnosed cases were found. Included were cases referred to the local department of cardiology, as well as cases treated in non-specialized departments. Of 132 cases found 23 were only diagnosed post mortem. The male/female ratio was 71/61. The median prehospital duration of symptoms was 20 days (range 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
41
5
7

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 0 publications
8
41
5
7
Order By: Relevance
“…The tendency was already seen in a study of IE from the Mayo Clinic in 1983, with the occurrence declining from 53% during the 1950s to 38% during the 1970s [21]. Compared to recent European studies, our finding of 38.9% S. aureus IE is remarkably high, and also compared to the Scandinavian studies by Nissen et al and Hogevik who found S. aureus in 28.8% and 31% respectively [9,20]. In a US study, 39.8% of the episodes of IE were due to S. aureus infections, but the study population consisted of 11.5% intravenous drug misusers [5].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The tendency was already seen in a study of IE from the Mayo Clinic in 1983, with the occurrence declining from 53% during the 1950s to 38% during the 1970s [21]. Compared to recent European studies, our finding of 38.9% S. aureus IE is remarkably high, and also compared to the Scandinavian studies by Nissen et al and Hogevik who found S. aureus in 28.8% and 31% respectively [9,20]. In a US study, 39.8% of the episodes of IE were due to S. aureus infections, but the study population consisted of 11.5% intravenous drug misusers [5].…”
Section: Discussionsupporting
confidence: 69%
“…As mentioned in the Danish study by Nissen et al, there is a high level of dental hygiene and a high focus on antibiotic prophylaxis in Denmark [20]. Another explanation could be that because this study was retrospective, medical records may lack information about dental procedures.…”
Section: Discussionmentioning
confidence: 87%
“…Las válvulas protésicas, cardiopatías congénitas, cardiopatías degenerativas esclerocálcicas y marcapasos cardiacos, son las otras patologías cardiacas de base, que van en paralelo a los cambios epidemiológicos ocurridos en los últimos tres a cuatro decenios [4][5][6][7][8] . La ausencia de daño cardiaco estructural en enfermos con EI, se observó en 26,1% de ellos en el examen ecocardiográfico.…”
Section: Seguimientounclassified
“…En EI por Pseudomona aeuriginosa, Enterobacteriaceas y hongos, esta mortalidad puede superar el 50% de los casos durante el período intrahospitalario. En una reciente comunicación del grupo del Estudio Colaborativo Internacional de EI (ICE-PCS), la mortalidad durante el episodio agudo fue de 17,7% 5 , a pesar de los avances crecientes en infectología, los altos estándares en aplicación para la técnica de los hemocultivos (automatización), los nuevos y poderosos antibióticos que se emplean en la actualidad en esta enfermedad [6][7][8][9][10] , de la incorporación de nuevas técnicas diagnósticas imagenológicas, entre las que se destaca, especialmente la ecocardiografía [11][12][13][14][15][16][17][18][19] ; los nuevos y estrictos criterios diagnósticos que se han incorporado [20][21][22] y el perfeccionamiento de las técnicas cardioquirúrgicas, incluidos rigurosos controles pre e intraoperatorios, así como de los dispositivos intracardiacos en uso [23][24][25][26][27] , todos ellos factores que se suman para reducir la morbimortalidad de esta patología en las últimas décadas [28][29][30] , esta mortalidad continúa elevada.…”
unclassified
“…These reports reveal that cardiologic reasons, coagulation disorders, and vasculopathies are predominant in the aetiology of ischemic stroke in young adults [6][7]. Infective endocarditis is an infection of the endocardium layer of the heart with an incidence of 1.9 -6.2/100.000, and the causative agents may be bacteria, viruses, or fungi [8][9]. Antimicrobial therapy is quite challenging in IE and requires following certain rules.…”
Section: Discussionmentioning
confidence: 99%